Perlindungan Hukum Terhadap Pemenuhan Hak Keselamatan dan Kesehatan Kerja - Irwan Irwan; Saharuddin Saharuddin; Muh. Akbar Fhad Syahril; Suprapto Suprapto (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to find out the rights of workers according to Law No. 6 of 2023 concerning Job Creation and to find out about Legal Protection for Occupational Safety and Health According to Legislation at PB Medina in Sidenreng Rappang Regency. The type of research used is the type of research used in this research is normative and empirical research or commonly known as legal research which combines the two. Based on the analysis of data and facts from research results and discussion, as follows: Some of the articles regulated in Law Number. 11 of 2020 concerning Job Creation has not sufficiently regulated the issue of labor rights. For example, those that regulate Work Agreements for a Specific Time (PKWT), wages, provincial or district/city minimum wages, serious errors in layoffs by workers/laborers, and the right to apply for labor if they feel disadvantaged. The Labor Law, which was 17 years old until the entry into force of the Job Creation Law, is currently unable to answer issues regarding labor rights and is considered very detrimental. The implementation of labor protection at Rice Milling Madina Sidenreng Rappang has been carried out by using the application of an occupational safety and health system. aims to provide security, safety, and health at work. The company protects all workers by providing work safety and security equipment and guidance regarding using PPE (Personal Protective Equipment). However, in practice, the application of OSH has not been carried out optimally, this is evidenced by the presence of workers/laborers who do not follow the SOPs applied by the company by not using personal protective equipment while working.